Удосконалення якості підготовки інженерних кадрів для технічного сервісу машин АВП - Гараєв, П. І.; Смєлов, Андрій Олександрович; Смелов, Андрей Александрович; Smielov, Andrii (ТДАТУ, 2017)
Uk: Досліджується поняття якість підготовки випускника ВНЗ, проблеми керування якістю підготовки фахівця. В цьому контексті пі-дкреслюється, що сьогоднішня реальність змушує переосмислити питання підготовки фахівців тому що, в нинішніх умовах від них потрібен професіо-налізм і компетентність при прийнятті самостійних рішень із розумним ри-зиком і економічним мисленням. Робиться висновок, що якість базової підгото-вки фахівця повинна забезпечити можливість фахівця обновляти якості, що част-ково втрачаються, або ж здобувати нові, є необхідність безперервного навчання. En: The authors studies the concepts of the quality of the graduate training of a university, the problems of quality management of specialist training. In this context, it is emphasized that today's reality forces us to rethink the question of training specialists because, in the current conditions, they require professionalism and competence in making independent decisions with reasonable risk and economic thinking. It is concluded that the quality of the basic training of a specialist should provide an opportunity for a specialist to update the qualities that are partially lost, or to acquire new ones, that is, the need for continuous training.
Іmprovement of quality of engineering training for technical service machines APV
Keywords: quality; specialist; professionalism; competence; continuity of training; practical training; якість; фахівець; професіоналізм; компетентність; безперервність навчання; практична підготовка